Potential of Sandless Geopolymer Concrete Bricks for Soundproof Walls - Masrafat, Hazen; Nurfain, Irfan; Bayuaji, Ridho; Tajunnisa, Yuyun; Alfayet, Muhamad Rifki (Department of Civil Engineering, Faculty of Engineering, Universitas Brawijaya, 2026)
This research explores the potential of sandless geopolymer bricks for application as soundproofing wall material. In this study, fly ash was employed as the primary binder in geopolymer concrete to substitute Portland cement, thereby reducing the environmental burden associated with conventional cement production. The geopolymer mixtures were prepared using a dry-mixing approach with varying proportions of coarse aggregate and binder. Three aggregate size ranges were investigated, namely 0.1–0.3 cm, 0.3–0.5 cm, and 0.5–1.0 cm. The performance of the resulting geopolymer concrete was evaluated through compressive strength, density, and sound transmission tests. The experimental results showed that specimens with larger aggregate sizes tended to exhibit higher compressive strength and density. In contrast, improved sound absorption was mainly associated with the development of pore structures within the material. These findings suggest that sandless geopolymer bricks have potential as an environmentally friendly material for soundproofing applications.